PERAN KEPALA MADRASAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI MADRASAH ALIYAH (MA) DARUL IHSAN SAMARINDA - Alisa Nurhasanah Salam; Mukhamad Ilyasin; Badrut Tamam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the fact that there are still some teachers who lack discipline, especially in terms of punctuality of attendance at MA Darul Ihsan Samarinda. This study aims to find out the role of madrasah heads in improving teacher discipline and the impact of the policies implemented. The research method used is qualitative descriptive with data sources for madrasah heads, deputy madrasah heads, teachers, and students. Data collection techniques are carried out through observation, interviews, and documentation, while data validity uses triangulation of sources and techniques. Data analysis uses the Miles, Huberman, and Saldana models through data condensation, data presentation, and conclusion drawn. The results of the study show that the head of the madrasah plays a role as a leader by providing an example to teachers, as an educator by providing an understanding that the teacher is an example for students, as a manager through the teaching supervision program, and as a supervisor by checking the teaching journal and the presence of teachers. The policy of the head of the madrasah has a positive impact on improving teacher discipline and is considered not burdensome. However, the implementation of the policy still faces several obstacles so that the firmness of the madrasah head is needed so that all teachers can be disciplined and create a conducive and orderly madrasah environment.